Existentialism and Moral Responsibility in Christian Religious Education: A Philosophical and Pedagogic Analysis - Nenometa, Marselin; Mooy, Jeremi; Banesi, Delvi; Mooyhana, Tiwani; Pellokila, Ireni Irnawati (JUPE : Jurnal Pendidikan Mandala, 2026)
Existentialism is a philosophical movement that emphasizes human freedom, choice, and responsibility for one’s existence. In the context of modern education, particularly Christian Religious Education (CRE), an existentialist approach is relevant for shaping students as conscious, reflective, and morally responsible individuals in faith. This article aims to analyze the basic concepts of existentialism, the thoughts of its major figures, and their implications for general education and Christian Religious Education. This study employs a qualitative descriptive method through library research. The findings indicate that existentialism contributes positively to the development of authentic faith and personal responsibility among students; however, its application must be critically filtered to remain consistent with Christian theology and biblical values.